Size-segregated particulate matter and gaseous emissions from motor vehicles in a road tunnel - Alves, Célia A.
In order to address road traffic emissions, studies need to be performed under realistic driving conditionswhere the input fromother sources isminimised.Measurements in traffic tunnels have been used for quantifying emissions, but so far no study has established emission factors (EFs) for Southern Europe. To fill this gap, a sampling campaign was carried out for one week in the Liberdade Avenue tunnel (Braga, Portugal). The campaign included the monitoring of gaseous pollutants (CO2, CO, NOx) and suspended particulate matter (PM) at two sites, one in the tunnel and another in an urban background location. Organic and elemental carbon (OC and EC) in sizesegregated particles (PM0.5, PM0.5–1, PM1–2.5 and PM2.5–10) were determined by a thermal–optical system, whereas major and trace elements were analysed by ICP-MS and ICP-AES. PM0.5 accounted for 56% of the PM10 mass, while PM2.5–10 represented only 12%. The carbonaceous fraction was concentrated in PM0.5, encompassing 88% of the EC and 67% of the OC present in PM10. Elements attributable to non-exhaust emissions could be divided into two groups. Fe, Ba, Cu, Sb, Sn and Zn, fromtyre and brakewear,weremore abundant in particles between 1 and 2 μm. Ca, Al, K, Sr and Ti, associated with soil resuspension,weremainly present in particles N2 μm. The average EFs of CO, CO2 and NOxwere 212, 4.02 and 1.22 g veh−1 km−1, respectively, while values of 152 mg PM10 veh−1 km−1 and 133 mg PM2.5 veh−1 km−1 were obtained for the particles. OC and EC emission factor was 39 mg veh−1 km−1 for PM10. The corresponding OC and EC values for PM2.5 were 34 and 38 mg veh−1 km−1. The EFs are slightly lower than those found for other tunnels, but within the ranges presented by the EMEP/EEA inventory.